SIGNIFICANCE OF CONIOPTERIS AND CZEKANOWSKIALES FOR THE JURASSIC STRATIGRAPHY OF WEST SIBERIAN CONTINENTAL DEPOSITS - Kirichkova A.I.; Bystritskaya L.I.; Travina T.A. (My University, 2002)
The detailed taxonomy of Czekanowskiales and genus Coniopteris dominating in Jurassic paleoflora of West Siberia, composition and stratigraphic confinement of their assemblages, and species of a restricted stratigraphic range are considered. Combinations of Coniopteris, Phoenicopsis, and Czekanowskia species characteristic of certain age intervals are first recognized. These combinations may be used for stratigraphic subdivision and correlation of West Siberian continental deposits.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская